Bridging Educational Neuroscience and Instructional Practice in Primary Schools through Teachers’ Neuropedagogic Understanding - Martatiyana, Diana Rossa; Supena, Asep (International Journal of Multidisciplinary Research and Innovation, 2025)
The development of educational neuroscience has provided an increasingly comprehensive understanding of learning as the result of interactions among biological, emotional, social, and environmental factors. Nevertheless, the application of neuroscientific findings in instructional practices at the elementary school level continues to face various challenges. This study aims to bridge educational neuroscience and classroom practice by analyzing elementary school teachers' understanding and implementation of neuropedagogical principles. A mixed methods approach with an embedded design was employed, integrating quantitative and qualitative data. Quantitative data were collected through a Likert-scale questionnaire to identify trends in brain-based instructional practices, while qualitative data were obtained through semi-structured interviews to explore teachers' pedagogical experiences and reflections. The findings indicate that teachers' instructional practices are largely aligned with principles of educational neuroscience, particularly in the management of emotional readiness, multisensory learning, and attention regulation. These results underscore that the primary challenge in implementing neuropedagogy lies not in teaching practices themselves, but in teachers' literacy in educational neuroscience. Strengthening teachers' conceptual understanding has a recognized potential to optimize existing practices, making them more systematic, reflective, and sustainable in supporting the cognitive, emotional, and social development of elementary school students.